If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.18(12) + 0.02x = 0.06(24 + x) Multiply 0.18 * 12 2.16 + 0.02x = 0.06(24 + x) 2.16 + 0.02x = (24 * 0.06 + x * 0.06) 2.16 + 0.02x = (1.44 + 0.06x) Solving 2.16 + 0.02x = 1.44 + 0.06x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.06x' to each side of the equation. 2.16 + 0.02x + -0.06x = 1.44 + 0.06x + -0.06x Combine like terms: 0.02x + -0.06x = -0.04x 2.16 + -0.04x = 1.44 + 0.06x + -0.06x Combine like terms: 0.06x + -0.06x = 0.00 2.16 + -0.04x = 1.44 + 0.00 2.16 + -0.04x = 1.44 Add '-2.16' to each side of the equation. 2.16 + -2.16 + -0.04x = 1.44 + -2.16 Combine like terms: 2.16 + -2.16 = 0.00 0.00 + -0.04x = 1.44 + -2.16 -0.04x = 1.44 + -2.16 Combine like terms: 1.44 + -2.16 = -0.72 -0.04x = -0.72 Divide each side by '-0.04'. x = 18 Simplifying x = 18
| 8+19n-3=7n+89-2n | | 2(3x-4)=5(8-2x) | | 7(2x-1)=3(15-4x) | | 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 |